PENGARUH E-WOM DAN PROMOSI MEDIA SOSIAL TERHADAP MINAT BELI ULANG PADA SHOPEE PADA MAHASISWA UNIVERSITAS KAPUAS SINTANG - Damiana, Damiana (Universitas Kapuas Sintang, 2025)
This study aims to determine (1) The simultaneous effect of E-WOM and social media promotion on repurchase intention in Shopee, (2) The effect of E-WOM on repurchase intention at Shopee (3) The effect of Social Media Promotion on repurchase intention at Shopee. The sampling technique used in this research is non-probability sampling with purposive sampling technique. The data in this study were obtained by distributing questionnaires in the form of google forms about E-WOM, social media promotion, and repurchase intention which were distributed to 100 respondents. Data analysis techniques used in this study are descriptive analysis, classical assumption test, and multiple linear regression analysis supported by using the program multiple linear regression analysis supported by using the SPSS statistics 25.0. The results of this study indicate that: (1) E-WOM and social media promotions simultaneously affect repurchase intention at Shopee. (2) E-WOM affects repurchase intention at Shopee. (3) Social media promotion affects repurchase intention at Shopee.